Idiopathic Premature Ventricular Contraction Conducting over a Ventricle Myocardial Extension from the Pulmonary Artery. Issue 10 (23rd June 2016) - YAMASAKI, HIRO; BERTAGNOLLI, LIVIO; HINDRICKS, GERHARD; ARYA, ARASH
Abstract : Ventricle myocardial extensions (VMEs) from the right ventricular outflow tract to the pulmonary artery (PA) serve as arrhythmogenic foci for idiopathic ventricular arrhythmias (VAs). Although an autopsy study revealed the heterogeneity of the VME, only the electrocardiographic features of PA‐VAs arising from septal VMEs have been discussed. Here, we describe a case of idiopathic PA‐VAs conducting over a VME accompanied by unique ventricle activation patterns, which contributed to the appearance of an S wave in the inferior limb leads despite an arrythmogenic focus in the outflow tract.